2020
DOI: 10.1371/journal.pone.0225015
|View full text |Cite
|
Sign up to set email alerts
|

Towards implementation of AI in New Zealand national diabetic screening program: Cloud-based, robust, and bespoke

Abstract: Convolutional Neural Networks (CNNs) have become a prominent method of AI implementation in medical classification tasks. Grading Diabetic Retinopathy (DR) has been at the forefront of the development of AI for ophthalmology. However, major obstacles remain in the generalization of these CNNs onto real-world DR screening programs. We believe these difficulties are due to use of 1) small training datasets (<5,000 images), 2) private and 'curated' repositories, 3) locally implemented CNN implementation methods, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Previously we have demonstrated that it is possible to train an artificial intelligence (AI) deep learning (DL) algorithm on retinal images to grade diabetic retinopathy and maculopathy for diagnostic, screening and risk assessment purposes [30,[36][37][38][39][40][41][42][43][44][45]. In this study we used 110,272 fundus images from a database of 55,118 patients from the UK Biobank and AREDS 1 datasets to train and subsequently test a novel AI platform (CVD-AI) to calculate a 10-year CVD risk score for these individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we have demonstrated that it is possible to train an artificial intelligence (AI) deep learning (DL) algorithm on retinal images to grade diabetic retinopathy and maculopathy for diagnostic, screening and risk assessment purposes [30,[36][37][38][39][40][41][42][43][44][45]. In this study we used 110,272 fundus images from a database of 55,118 patients from the UK Biobank and AREDS 1 datasets to train and subsequently test a novel AI platform (CVD-AI) to calculate a 10-year CVD risk score for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the prevalence of low-quality images, a deep learning image quality screening system was used to separate the images into high quality, medium quality, and low-quality images. The training dataset for the image quality screening system was in a similar manner to our prior THEIA system [30]. After the screening process there were 95,992 images from 51,956 patients (Figure 1).…”
Section: Data Preparationmentioning
confidence: 99%
“…In order to subtract local mean color from image, image was processed through equation1. 8 and saturated. With splitting the color channels, the green channel could be used for CLAHE processing or the image could be converted to a gray-scale/binary image.…”
Section: Image Processing Methodsmentioning
confidence: 99%
“…National attendance at screening usually falls below recommended rates, particularly for Māori, Pacific and remote communities. 135 Artificial intelligence technology offers ever improving methods to analyse fundus images faster, with greater accuracy and at lower cost than clinicians or technicians.…”
Section: Dovepressmentioning
confidence: 99%